IDENTIFIKASI DAN UJI SENSITIVITAS ANTIBIOTIK TERHADAP Pseudomonas aeruginosa DAN Klebsiella pneumoniae DARI SAMPEL ULKUS PASIEN DIABETES MELITUS - Eka Febrianti; Nony Puspawati; Dionysius A ndang Arif Wibawa (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
Diabetic ulcers are one of the serious complications in patients with diabetes mellitus, who are highly susceptible to infections caused by pathogenic bacteria, particularly gram-negative bacteria such as Pseudomonas aeruginosa and Klebsiella pneumoniae. Infection management requires identification of the causative bacteria and antibiotic sensitivity testing to determine effective therapy. This study aims to identify the presence of Pseudomonas aeruginosa and Klebsiella pneumoniae in ulcer samples from diabetes mellitus patients and to determine their sensitivity patterns to several types of antibiotics. The research employed a laboratory-based observational method with a cross-sectional approach to describe the presence of Pseudomonas aeruginosa and Klebsiella pneumoniae as well as their antibiotic sensitivity based on test results from ulcer samples of diabetic patients. The samples were collected from diabetic patients with ulcers. Bacterial isolation and identification were carried out through gram staining and standard biochemical tests. Antibiotic sensitivity testing was performed using the Kirby-Bauer (disk diffusion) method against imipenem, ciprofloxacin, gentamicin, and ampicillin. The results of the study showed that from a number of samples analyzed, positive isolates of Pseudomonas aeruginosa and Klebsiella pneumoniae were found, in the study respondents, around 70% were male and aged over 50 years. Sensitivity tests showed that Pseudomonas aeruginosa had high sensitivity to imipenem but resistance to ampicillin. Klebsiella pneumoniae showed sensitivity to ciprofloxacin, but some isolates showed resistance to ampicillin.